Study on Satisfactions of Primary Teachers for Undergraduate Level Year 3 on Methods of Teaching Arts and Crafts at Dongkhamxang Teacher Training College - CHANTHABOULY, Kongseng; PHUANGLASON , Sonchai; SOUVANNABANDITH, Souphaphern (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The purpose of this research was to 1) study the satisfaction of the primary trainee teachers with the teaching of art and handicrafts methodology. 2) to comparing the satisfaction of female students and male students in the 3rd year undergraduate teacher training students with the teaching art and handicrafts methodology. This research has a total population of 93 people and 60 females. The sample group consisted of 76 people and 50 females by the way of Taro YAMANE, the sample group who were the 3rd year undergraduate teacher training students in Dongkhamxang Teacher Training College in academic year 2019-2020. The data collection tool was a questionnaire for study on satisfaction of elementary teacher training students with learning of art and handicrafts methodology that consist of 5 items and 36 questions. The variability value is 0.94. The statistics used in the data analysis were percentage, mean, standard deviation, t-test and pair comparison by the way of schaeffer.The research found that: Satisfaction of the 3rd year undergraduate teacher training students with the teaching of Arts and Crafts methodology were high level in all 5 items by according to the high to low average: personality, curriculum, teaching and learning management, learning environmental, measurement and evaluation. Female undergraduate students in the 3rd year are satisfied with the teaching of art and crafts methodology whereas different from male students with a statistically significant level of 0.05